All Librarianship is Political: Educate Accordingly - Paul T. Jaeger; Lindsay C Sarin (The Political Librarian, 2016)
After participating in a multi-year project considering the future directions for library and information science (LIS) education, the authors of this paper realized an essential aspect of the nature of libraries and librarianship was continually overlooked or sidestepped in the events and discussions. That is, libraries as institutions and many of the actions of library professionals are inherently political, yet LIS education has not traditionally prepared students for them. Confronting this aspect of LIS education and the profession in general and creating curriculum that emphasizes the politics of librarianship will better prepare students to serve their patrons, their communities, and their institutions. Such an educational approach would emphasize preparing future library professionals in areas such as leadership, education, activism and advocacy, community service and engagement, policy and law, rights and justice, and marketing and evaluation, resulting in the politically-savvy librarians ready to be activists for their institutions and communities. This paper explores the design of library education, criticism of library education, and the actual environment of contemporary librarians as the context for suggesting this significant change in the focus of library education. We live in a political world, and it’s time we prepare our students for this world.